2021
DOI: 10.3390/app112210583
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Cortical Bone Trajectory Fixation with Traditional Pedicle Screw in the Lumbar Spine: A Finite Element Study

Abstract: Cortical bone trajectory (CBT) is increasingly used in spinal surgery. Although there are many biomechanical studies, the biomechanical effect of CBT in combination with traditional pedicle screws is not detailed. Therefore, the purpose of this study was to investigate the effects of the traditional pedicle screw and CBT screw implantation on the lumbar spine using finite element methods. Based on the combination of the traditional pedicle screw and the CBT system implanted into the lumbar spine, four finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…In this study, As for the BPS-BMCS group, the von Mises stress of the screw was lower than those of the BPS-BPS group in motion. As for the BMCS-BPS group, the von Mises stress of the screw was lower than that in the BPS-BPS group in exion, extension, and rotation and the stress variation rules were comparable to those of Su et al [31], BPS-BMCS group and BMCS-BPS group may reduce the incidence of screw breakage. The lowest screw stress was found in the BPS-BMCS (30.12 ± 5.73 MPa) and BMCS-BPS (32.79 ± 4.63 MPa) group in exion.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In this study, As for the BPS-BMCS group, the von Mises stress of the screw was lower than those of the BPS-BPS group in motion. As for the BMCS-BPS group, the von Mises stress of the screw was lower than that in the BPS-BPS group in exion, extension, and rotation and the stress variation rules were comparable to those of Su et al [31], BPS-BMCS group and BMCS-BPS group may reduce the incidence of screw breakage. The lowest screw stress was found in the BPS-BMCS (30.12 ± 5.73 MPa) and BMCS-BPS (32.79 ± 4.63 MPa) group in exion.…”
Section: Discussionsupporting
confidence: 70%
“…Increasing the medio-lateral angle of the pedicle screw reduced the risk of screw loosening and breakage [30]. Peak von mises stress of the screw in the hybrid xation technique with CBT and pedicle screw, in Su et al [31], were lower than that of the BPS-BPS technique in exion, extension, and lateral bending. In this study, As for the BPS-BMCS group, the von Mises stress of the screw was lower than those of the BPS-BPS group in motion.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…After the mesh convergence test, the mesh size used in this study is 4 mm. All 12 finite element mesh models reached 5% of the stop criteria of convergence test when mesh size convergence test was used [26]. Therefore, the finite element mesh model used in this study was rational.…”
Section: Materials Properties Of the Modelmentioning
confidence: 97%
“…In this study only static loading conditions were tested. Su et al [18] investigated the effects of the traditional pedicle screw and cortical bone trajectory screw implantation on the lumbar spine using FE methods. The results showed that there was no significant difference in the structural stability of the lumbar spine model between the traditional pedicle screw system and the cortical bone trajectory system.…”
Section: Introductionmentioning
confidence: 99%